2020
DOI: 10.7759/cureus.11669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ureteral Stent Length and Position of Stent Coil in Bladder on Stent-Related Symptoms and Quality of Life of Patients

Abstract: Introduction: Various standardized questionnaires can evaluate ureteral stent-related symptoms. The present study utilized a validated instrument, Ureteral Stent Symptoms Questionnaire (USSQ), to know the impact of the length of double J stent (DJS) in comparison to ureter length on patients and their quality of living. Materials and Method: This study is a prospective clinical study conducted in the Department of Urology at a tertiary care center in South India. Patients who underwent DJS after endoscopic ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Furthermore, AL-KANDARI et al research (8), which included 120 individuals, reported that 53 individuals (88%) in the contralateral group had moderate to severe dysuria compared to 11 individuals (18%) in the ipsilateral group (P < 0.001). It was noteworthy that correct intravesical stent placement has been repeatedly proven to improve the USRS (13,26,27). Thus we included 6 studies with 590 individuals to explore the impact of stent position on the USRS using a meta-analysis of USSQ, IPSS, and QoL score.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, AL-KANDARI et al research (8), which included 120 individuals, reported that 53 individuals (88%) in the contralateral group had moderate to severe dysuria compared to 11 individuals (18%) in the ipsilateral group (P < 0.001). It was noteworthy that correct intravesical stent placement has been repeatedly proven to improve the USRS (13,26,27). Thus we included 6 studies with 590 individuals to explore the impact of stent position on the USRS using a meta-analysis of USSQ, IPSS, and QoL score.…”
Section: Discussionmentioning
confidence: 99%
“…After further examination of the full-text, 4 articles (8,9,12,24)were excluded due to the absence of available data. The remaining 6 papers (13)(14)(15)(25)(26)(27)were eventually included in the metaanalysis. Three of the included studies were randomized controlled trials (RCTs) (13,14,25), and three were prospective observational studies (15,26,27).…”
Section: Characteristics Of the Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations